Shared Predicament of Nature and Motherhood in Kamala Markandaya’s Nectar in a Sieve - Sharma, Kamal (The Batuk, 2021)
This paper examines and analyses conflating relation of nature and motherhood in Kamala Markandaya's Nector in a Sieve by applying ecofeminist perspective. The novel revolves around a central character called Rukmani who struggles hard to survive and sustain her family working in the field. Her misery begins to unfold due to infertility she bears. Her daughter, Ira faces the same problem her mother had faced. It almost ruins Rukmani’s life. She is always obsessed with motherhood, nurturing qualities, and natural surrounding around her. This paper explores why motherhood always bothers Rukmani thereby showing her bonding and belonging to nature. This paper being qualitative in nature applies ecofeminist theories for the textual analysis of the primary. The paper concludes that Rukmani’s struggles in reproduction and her strong will to be in land community asserts the shared predicament of nature and motherhood where she is more obsessed with her biological role of mother.